Optimal methotrexate dose is associated with better clinical outcomes than non-optimal dose in daily practice: results from the ESPOIR early arthritis cohort. Issue 12 (2nd September 2017) - Gaujoux-Viala, Cécile; Rincheval, Nathalie; Dougados, Maxime; Combe, Bernard; Fautrel, Bruno
Abstract : Background: Although methotrexate (MTX) is the consensual first-line disease-modifying antirheumatic drug (DMARD) for rheumatoid arthritis (RA), substantial heterogeneity remains with its prescription and dosage, which are often not optimal. Objective: To evaluate the symptomatic and structural impact of optimal MTX dose in patients with early RA in daily clinical practice over 2 years. Methods: Patients included in the early arthritis ESPOIR cohort who fulfilled the ACR-EULAR (American College of Rheumatology/European League against Rheumatism) criteria for RA and received MTX as a first DMARD were assessed. Optimal MTX dose was defined as ≥10 mg/week during the first 3 months, with escalation to ≥20 mg/week or 0.3 mg/kg/week at 6 months without Disease Activity Score in 28 joints remission. Symptomatic and structural efficacy with and without optimal MTX dose was assessed by generalised logistic regression with adjustment for appropriate variables. Results: Within the first year of follow-up, 314 patients (53%) with RA received MTX as a first DMARD (mean dose 12.2±3.8 mg/week). Only 26.4% (n=76) had optimal MTX dose. After adjustment, optimal versus non-optimal MTX dose was more efficient in achieving ACR-EULAR remission at 1 year (OR 4.28 (95% CI 1.86 to 9.86)) and normal functioning (Health Assessment Questionnaire ≤0.5; OR at 1 year 4.36 (95% CI 2.03 to 9.39)), with no effect on radiological progression. Results were similar during the second year. Conclusion: Optimal MTX dose is more efficacious than non-optimal dose for remission and function in early arthritis in daily practice, with no impact on radiological progression over 2 years.